Oscillation Criteria for Nonlinear Third-Order Neutral Dynamic Equations with Damping on Time Scales. (28th August 2017) - Qiu, Yang-Cong; Zada, Akbar; Qin, Haiyong; Li, Tongxing
Abstract : We establish several oscillation criteria for a class of third-order nonlinear dynamic equations with a damping term and a nonpositive neutral coefficient by using the Riccati transformation. Two illustrative examples are presented to show the significance of the results obtained.